Patch clamp studies on TRPV4-dependent hemichannel activation in lens epithelium - Ek-Vitorin, Jose F.; Shahidullah, Mohammad; Lopez Rosales, Joaquin E.; Delamere, Nicholas A. (Frontiers in Pharmacology, 2023)
ATP release from the lens via hemichannels has been explained as a response to TRPV4 activation when the lens is subjected to osmotic swelling. To explore the apparent linkage between TRPV4 activation and connexin hemichannel opening we performed patch-clamp recordings on cultured mouse lens epithelial cells exposed to the TRPV4 agonist GSK1016790A (GSK) in the presence or absence of the TRPV4 antagonist HC067047 (HC). GSK was found to cause a fast, variable and generally large non-selective increase of whole cell membrane conductance evident as a larger membrane current (Im) over a wide voltage range. The response was prevented by HC. The GSK-induced Im increase was proportionally larger at negative voltages and coincided with fast depolarization and the simultaneous disappearance of an outward current, likely a K+ current. The presence of this outward current in control conditions appeared to be a reliable predictor of a cell’s response to GSK treatment. In some studies, recordings were obtained from single cells by combining cell-attached and whole-cell patch clamp configurations. This approach revealed events with a channel conductance 180-270 pS following GSK application through the patch pipette on the cell-attached side. The findings are consistent with TRPV4-dependent opening of Cx43 hemichannels.